Pengaruh Massa dan Kecepatan Kendaraan Terhadap Suhu Pada Rem Drum - Ridwan Ridwan; Afrizal Riyantono; Rudi Irawan (Jurnal Sinergi Jurusan Teknik Mesin, 2023)
Brakes are a tool for slowing down or stopping a vehicle while it's in motion. They also serve as a safety mechanism when a vehicle is parked or at a stop. Brakes can convert kinetic and potential energy into heat through the frictional process between brake pads and the rotor, leading to heat transfer. In the world of transportation, analyzing the heat generated by the vehicle's brakes is a crucial process for evaluating and enhancing braking system performance. In this study, simulations were conducted on the brake rotor (drum brake) of a minibus with vehicle masses of 3500 kg and 5000 kg, using Abaqus software. Five different speed variations were considered: 60 km/h, 70 km/h, 80 km/h, 90 km/h, and 100 km/h. The simulation results for the vehicle with a mass of 3500 kg showed progressively increasing maximum temperatures in the brake rotor: 87.82°C, 106.55°C, 163.69°C, 216.34°C, and 275.04°C for the respective speeds. In the simulation with a vehicle mass of 5000 kg, the maximum rotor temperatures were 108.45°C, 126.33°C, 207.9°C, 269.03°C, and 299.31°C. Higher braking speeds result in higher heat generation in the brake rotor. However, the temperature increase is not linear concerning vehicle speed. The vehicle's mass significantly influences the heat generated in the rotor during braking. At the same speed, a higher-mass vehicle will produce more heat.